Is Enterprise Architecture Management System (EAMS) In Tron Storage Successful In Improving The It Service Lifecycle? - Ho, Jenny Pei Lee (2014)
This case study is a research to identify problems faced by Enterprise Architecture (EA) Team in implementing decision making tool in company and challenges faced in bringing to tool to maturity. The tool implemented by EA Team is Enterprise Architecture Management System (EAMS) which is a commercial product to help huge enterprise align their IT Applications with their business goals. Successful implementation of the tool will enable the organization to achieve agility in the changing business requirements and make fast accurate decision. The success factor of the tool is very intangible and organization do not see fast effect after purchasing the tool.